(untitled) (Rudarsko-geološko-naftni zbornik, 2016)
The theme of this paper are the Croatian terms for schist – škriljac, škriljevac or škriljavac, and for schistose – škriljav or škriljast. Linguistic and professional sources are not uniformed, so from the aspect of word formation, it is discussed which terms fit into the terminological system the best.